Impact of sonochemical synthesis condition on the structural and physical properties of MnFe2O4 spinel ferrite nanoparticles - Yadav, Raghvendra Singh; Kuřitka, Ivo; Vilčáková, Jarmila; Jamatia, Thaiskang; Machovský, Michal; Škoda, David; Urbánek, Pavel; Masař, Milan; Urbánek, Michal; Kalina, Lukáš; Havlica, Jaromír (ELSEVIER, 2020)
Herein, we report sonochemical synthesis of MnFe2O4 spinel ferrite nanoparticles using UZ SONOPULS HD 2070 Ultrasonic homogenizer (frequency: 20 kHz and power: 70 W). The sonication time and percentage amplitude of ultrasonic power input cause appreciable changes in the structural, cation distribution and physical properties of MnFe2O4 nanoparticles. The average crystallite size of synthesized MnFe2O4 nanoparticles was increased with increase of sonication time and percentage amplitude of ultrasonic power input. The occupational formula by Xray photoelectron spectroscopy for prepared spinel ferrite nanoparticles was (Mn0.29Fe0.42[Mn0.71Fe1.58]O-4 and (Mn0.28Fe0.54) [Mn0.72Fe1.46]O-4 at sonication time 20 min and 80 min, respectively. The value of the saturation magnetization was increased from 1.9 emu/g to 52.5 emu/g with increase of sonication time 20 min to 80 min at constant 50% amplitude of ultrasonic power input, whereas, it was increased from 30.2 emu/g to 59.4 emu/g with increase of the percentage amplitude of ultrasonic power input at constant sonication time 60 min. The highest value of dielectric constant (epsilon') was 499 at 1 kHz for nanoparticles at sonication time 20 min, whereas, ac conductivity was 368 x 10(-9) S/cm at 1 kHz for spinel ferrite nanoparticles at sonication time 20 min. The demonstrated controllable physical characteristics over sonication time and percentage amplitude of ultrasonic power input are a key step to design spinel ferrite material of desired properties for specific application. The investigation of microwave operating frequency suggest that these prepared spinel ferrite nanoparticles are potential candidate for fabrication of devices at high frequency applications.

Herein, we report sonochemical synthesis of MnFe2O4 spinel ferrite nanoparticles using UZ SONOPULS HD 2070 Ultrasonic homogenizer (frequency: 20 kHz and power: 70 W). The sonication time and percentage amplitude of ultrasonic power input cause appreciable changes in the structural, cation distribution and physical properties of MnFe2O4 nanoparticles. The average crystallite size of synthesized MnFe2O4 nanoparticles was increased with increase of sonication time and percentage amplitude of ultrasonic power input. The occupational formula by Xray photoelectron spectroscopy for prepared spinel ferrite nanoparticles was (Mn0.29Fe0.42[Mn0.71Fe1.58]O-4 and (Mn0.28Fe0.54) [Mn0.72Fe1.46]O-4 at sonication time 20 min and 80 min, respectively. The value of the saturation magnetization was increased from 1.9 emu/g to 52.5 emu/g with increase of sonication time 20 min to 80 min at constant 50% amplitude of ultrasonic power input, whereas, it was increased from 30.2 emu/g to 59.4 emu/g with increase of the percentage amplitude of ultrasonic power input at constant sonication time 60 min. The highest value of dielectric constant (epsilon') was 499 at 1 kHz for nanoparticles at sonication time 20 min, whereas, ac conductivity was 368 x 10(-9) S/cm at 1 kHz for spinel ferrite nanoparticles at sonication time 20 min. The demonstrated controllable physical characteristics over sonication time and percentage amplitude of ultrasonic power input are a key step to design spinel ferrite material of desired properties for specific application. The investigation of microwave operating frequency suggest that these prepared spinel ferrite nanoparticles are potential candidate for fabrication of devices at high frequency applications.
Impact of sonochemical synthesis condition on the structural and physical properties of MnFe2O4 spinel ferrite nanoparticles
Keywords: Spinel ferrite; Nanoparticles; Sonochemical synthesis; Magnetic property; Electrical property; Spinel ferrite; Nanoparticles; Sonochemical synthesis; Magnetic property; Electrical property